A rare case of duodenal cancer with achalasia cardia - Kartikesh Mishra (Society of Surgeons of Nepal, 2019)
Duodenal adenocarcinoma constitutes 0.4% of gastrointestinal malignancies. Achalasia incidence rate is 0.5-1.2 per 100000. The combination is rare.